2020
DOI: 10.1101/2020.09.13.295691
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ambroxol Hydrochloride Inhibits the Interaction between Severe Acute Respiratory Syndrome Coronavirus 2 Spike Protein’s Receptor Binding Domain and Recombinant Human ACE2

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), the causative agent of coronavirus disease 2019 (COVID-19), enters the host cells through two main pathways, both involving key interactions between viral envelope-anchored spike glycoprotein of the novel coronavirus and the host receptor, angiotensin-converting enzyme 2 (ACE2). To date, SARS-CoV-2 has infected up to 26 million people worldwide; yet, there is no clinically approved drug or vaccine available. Therefore, a rapid and coordinated effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 47 publications
0
21
0
3
Order By: Relevance
“…More likely, favorable patient outcomes are attributable to the beneficial effects of Bromhexine or its main metabolite Ambroxol on lung function, general defense mechanisms against airway infections, and inflammatory response (16–19, 50). Another recent study by Olaleye et al (21) specifically analyzed the effects of Bromhexine and Ambroxol on the interaction of ACE2 with the SARS-CoV-2 spike receptor binding domain (RBD), and reported a very peculiar behavior of these substances which in part may explain the paradoxic results of our fusion assays and would support a beneficial effect of low-dose Bromhexine, which is converted to Ambroxol in vivo : While Ambroxol weakly inhibited the ACE2-RBD interaction up to 100μM concentration, Bromhexine exhibited a biphasic behavior and was weakly inhibitory below 10μM but increased ACE2-RBD binding at higher concentrations in that study. Both substances were reported to weakly inhibit SARS-CoV-2-mediated cytopathic effect in culture (22), and Ambroxol was also shown to moderately impact replication of SARS-CoV-2 in that report (22), albeit on Vero cells and not lung cells.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…More likely, favorable patient outcomes are attributable to the beneficial effects of Bromhexine or its main metabolite Ambroxol on lung function, general defense mechanisms against airway infections, and inflammatory response (16–19, 50). Another recent study by Olaleye et al (21) specifically analyzed the effects of Bromhexine and Ambroxol on the interaction of ACE2 with the SARS-CoV-2 spike receptor binding domain (RBD), and reported a very peculiar behavior of these substances which in part may explain the paradoxic results of our fusion assays and would support a beneficial effect of low-dose Bromhexine, which is converted to Ambroxol in vivo : While Ambroxol weakly inhibited the ACE2-RBD interaction up to 100μM concentration, Bromhexine exhibited a biphasic behavior and was weakly inhibitory below 10μM but increased ACE2-RBD binding at higher concentrations in that study. Both substances were reported to weakly inhibit SARS-CoV-2-mediated cytopathic effect in culture (22), and Ambroxol was also shown to moderately impact replication of SARS-CoV-2 in that report (22), albeit on Vero cells and not lung cells.…”
Section: Discussionmentioning
confidence: 94%
“…Ambroxol may also exhibit weak but broad anti-viral activity as it was shown to reduce the occurrence of respiratory infections (17) and to inhibit proteolytic activation of influenza virus by triggering release of antiviral factors (18), and it is used to treat acute respiratory distress syndrome in adults and antenatally in infants (19, 20). Further, two recent preprints, one describing modulation of the ACE2-SARS2-S interaction by both Bromhexine and Ambroxol (21) and the other reporting weak inhibitory activity of Ambroxol against SARS-CoV-2 replication (22) in Vero E6 cells, point at a potential utility of these molecules in the therapy of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Bradfute et al demonstrated that ambroxol blocks Vero-E6 cells infection with SARS-CoV-2 ( 38 ). A study by Olaleye et al revealed that micromolar concentrations of ambroxol prevented cellular infections with SARS-CoV-2 determined as cytopathic effect of the virus ( 39 ). The authors further demonstrated using recombinant proteins of the receptor binding domain of spike and ACE2 that ambroxol interferes with the binding of SARS-CoV-2 spike with human ACE2 in vitro ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Olaleye et al revealed that micromolar concentrations of ambroxol prevented cellular infections with SARS-CoV-2 determined as cytopathic effect of the virus ( 39 ). The authors further demonstrated using recombinant proteins of the receptor binding domain of spike and ACE2 that ambroxol interferes with the binding of SARS-CoV-2 spike with human ACE2 in vitro ( 39 ). Thus, ambroxol may prevent infections with SARS-CoV-2 at different levels, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…[28,21]. А свежие экспериментальные исследования подтвердили способность бромгексина блокировать активность и основного клеточного рецептора АПФ-2 [29,22]. Более того, только что завершившееся контролируемое исследование с бромгексином на 78 пациентах продемонстрировало статистически значимое снижение перевода больных в отделение реанимации и интенсивной терапии (ОРИТ) (2 / 39 против 11 / 39, р=0,006), необходимость ИВЛ (1 / 39 против 9 / 39, р=0,007) и снижение смертности (0 против 5, р=0,027) [30,23].…”
Section: Discussionunclassified